Anatomia foliar e trocas gasosas de Miconia albicans (SW) Steud, Miconia ferruginata DC (Melastomataceae) em ambientes de cerrado e campo rupestre no Parque Ecológico Quedas do Rio Bonito - Morais, José Crispim Reis de (2020)
This work was conducted with the aim of analyzing and describing the leaf anatomy and gas exchange characteristics of Miconia albicans (Sw) Steud and Miconia ferruginata DC in the cerrado and campo rupestre, in order to identify traits of variability, modulators of leaf anatomy gas exchange, depending on the environmental variations in these phytophysiognomies. There were no significant differences by analysis of variance in the species Miconia albicans, however the species Miconia ferruginata had significant differences mainly in the case of campo rupestre. The species showed xeromorphic traces in both environments, such as: isobilateral mesophilic thickening, thick cuticle and thicker uniseriate epidermis on the adaxial face, dentritic trichomes, anisocytic and anomocytic stomata, plated palisade parenchyma, cells with recesses and stomach crypts. However, the species Miconia ferruginata from campo rupestre presents significant variables, as they have plasticity. High radiation, soil type and low relative humidity can be environmental modulating factors of leaf anatomy and gas exchange in these environments. With the result of this research, a possible metabolic adaptation of the studied plant is indicated, which may even significantly affect the anatomy and gas exchange.